Socio-economic development of Muslim women: Impact of education - Devi, Lakshmi (2014)
Education is one of the significant social indicators having bearing on the achievement and the growth of an individual as well as community. This is perceived to be highly suitable for providing employment and, thereby, improving the quality of life. The educational status of Muslim women in India is worse than that of Muslim men and women of other communities. They have the lowest work participation rate and most of them engage in the self-employment activities. The article suggests that state governments need to make special provisions, over and above the normal, for drawing and retaining Muslim girls in school till class 8th as a fundamental right, and for improving their participation in secondary and higher technical education and professional education, so that they can contribute effectively in the socio-economic development of the nation. - Reproduced.
Keywords: Education; Muslims; Women